Nursing care for a 41-year-old patient suffering from breast cancer in a hospital setting - Bogusława Ryś; Aleksandra Czul; Ewelina Bąk (Kazimierz Wielki University, 2024)
Breast cancer is the most common cause of cancer-related deaths among women in the world. Its occurrence is mainly influenced by environmental factors, and to a lesser extent by genetic factors. The gold standard in diagnosis is mammography, but special attention should be paid to the need to educate women at an increasingly younger age in the field of breast self-examination. Treatment for breast cancer includes surgery, radiotherapy, chemotherapy and hormone therapy.